-12b+b=3b+30

Simple and best practice solution for -12b+b=3b+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12b+b=3b+30 equation:


Simplifying
-12b + b = 3b + 30

Combine like terms: -12b + b = -11b
-11b = 3b + 30

Reorder the terms:
-11b = 30 + 3b

Solving
-11b = 30 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-11b + -3b = 30 + 3b + -3b

Combine like terms: -11b + -3b = -14b
-14b = 30 + 3b + -3b

Combine like terms: 3b + -3b = 0
-14b = 30 + 0
-14b = 30

Divide each side by '-14'.
b = -2.142857143

Simplifying
b = -2.142857143

See similar equations:

| 12x+30=6x-4 | | t=6+-0.6666666667T | | P-22=4-p+14 | | -11/5+(-7.8) | | -16+n=-15 | | 4444x-2200=44(101x-50) | | (5x+9)+6=-1 | | 9.x=3.5 | | -2(x+6)=-2x+5 | | -8=-6x+(5x-3) | | 4(3x+3)=17x+8-5x+4 | | Y/4=-7/1 | | 8-n=-10+6n-4n | | 2/3y+y=35 | | 25x^2+70xy+49y^2=0 | | 2/3x+8=24 | | 7x-6=-38+3x | | 3x^0/x^2 | | 5(x+3)=1+5x | | z=q-qab | | -8(-8)-8= | | x^2-12x=60 | | T-1/4=-3/4 | | q=p-q/2 | | z(z+2)=63 | | 9/5m=1/5 | | (8/(3x+1))-(27x/(3x-1))=-9 | | 9=6(-b+7)+7(b-5) | | k^3/2k^2 | | -2x+7-5x=-70 | | X+x+130=750 | | -5(8v-8)-4(5v+8)=8 |

Equations solver categories